VISITING TUAN TOSALAMA’S GRAVE IN BULO-BULO MANDAR: Max Scheler’s Value Hierarchy Perspective - Muh Ilham Usman; Abu Muslim (Balai Penelitian dan Pengembangan Agama Makassar, 2023)
AbstractThe purpose of this article is to examine the tradition of visiting Tuan Tosalama ri Bulo-bulo's grave and to learn more about the phenomenon of this practice. Observation and in-depth interviews were used in a descriptive qualitative methodology. Additionally, the data were examined using Max Scheler's value hierarchy methodology. The findings demonstrated that Tuan Tosalama ri Bulo-bulo, who lived in the 16th century, was thought to be the one who first spread Islam in the confederation area of Karua Tiparittiqna Uhai (eight drops of water from the mountain). The inhabitants of Bulo- bulo regularly visit the graves as pilgrims who have been purified. As a sign of appreciation and a salute to Tuan Tosalama ri Bulo-bulo, it has even become a yearly custom in the area following the rice harvest. Not only is visiting the tombs a ritual, but it also has philosophical benefits, including spiritual, psychological, and recreational ones. The abundance of cakes and food served in each house highlights the pleasure value of having fun. This pilgrimage tradition's main benefit is that it serves as a meeting place for migrants returning home and residents of Bulo-bulo. Following their visit to Tuan Tosalama ri Bulo-bulo's grave, pilgrims are said to experience inner peace, according to psychological values. While traveling, pilgrims develop spiritually and exhibit religious values.